Rapid and de-centralized model for municipal effluent reclamation using microalgae. Issue 1 (10th December 2020) - Palkar, Juilee; Navale, Mahesh; Lali, Arvind; Pandit, Reena
Abstract: Microalgal bioremediation is currently being venerated for its potential in municipal liquid waste (MLW) treatment. Algae-based water treatment with retention time competitive to the conventional water treatment processes is a challenge. The present study investigated the role of algal biomass concentration to improve treatment efficiency to reduce the time required for water treatment. Eighty percent removal of pollutants (in terms of chemical oxygen demand (COD), ammonia, phosphate and fecal coliforms) was obtained in 12 hours at a biomass concentration of 1 gL −1 . Further, continuous treatment of MLW using membrane-assisted photobioreactor was established. The treatment led to >95% removal of ammonia, >75% removal of COD and 100% removal of fecal coliforms within 12 hours. Physiological assessment of the algal culture showed that the cells did not manifest symptoms of stress throughout the reactor cycle, a consequence of continuous availability of the nutrients, maintaining the culture in continuous growth state. Highlights: De-centralization of water treatment. Rapid water treatment with retention time of 10 h. Photosynthetic systems for water treatment. Biomass produced which can be utilized for value-added products generation. Zero-waste discharge systems.